Environment-friendly heat-resistant glue and preparation method thereof

Through the combination of nano silica, organically modified montmorillonite and aminoglycoated graphene, an environmentally friendly heat-resistant glue was prepared, which solved the problem of insufficient stability and bonding strength of the existing glue in high temperature environments, and achieved efficient heat resistance and environmental protection performance.

CN119842342AActive Publication Date: 2025-04-18YUEYANG JINGWEI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510146263.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-18
Estimated Expiration
2045-02-10

Smart Images

  • Figure CN119842342A_ABST
    Figure CN119842342A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesive preparation, and particularly relates to environment-friendly heat-resistant glue and a preparation method thereof. The environment-friendly heat-resistant glue is prepared from the following raw materials in parts by weight: 80 to 100 parts of polyvinyl chloride, 3 to 6 parts of nano silicon dioxide, 4 to 8 parts of organic modified montmorillonite, 1 to 2 parts of aminated graphene, 5 to 10 parts of polycaprolactone, 5 to 10 parts of polylactic acid, 10 to 20 parts of plasticizer and 0.5 to 1 part of antioxidant. Through combination of the nano silicon dioxide, the organic modified montmorillonite and the aminated graphene, the heat resistance and the mechanical property of the glue are remarkably improved, the nano silicon dioxide provides thermal stability and mechanical support, the organic modified montmorillonite limits thermal movement of PVC, and the aminated graphene provides thermal conductivity and bonding strength; polycaprolactone and polylactic acid are used as flexibilizers to improve the flexibility and thermal stability, and all the components have a synergistic effect to ensure the stable performance of the glue in a high-temperature and harsh environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive preparation, and particularly relates to an environmentally friendly heat-resistant glue and a preparation method thereof. Background Art

[0002] As a common adhesive, glue is widely used in many fields such as industry, construction, furniture manufacturing, packaging, and electronic products. With the development of science and technology and changes in market demand, the performance requirements for glue are getting higher and higher, especially heat resistance and environmental protection. In many applications, glue needs to maintain good bonding performance under high temperature environment, such as automotive parts, aerospace, electronic equipment, etc. Traditional heat-resistant glues are mostly made of synthetic materials such as epoxy resin and phenolic resin. Although these materials have good heat resistance, they have certain problems in environmental protection and health. With the increasing global awareness of environmental protection, more and more industries have begun to pay attention to the environmental performance of products. Solvents, plasticizers and other ingredients commonly used in traditional glues may contain volatile organic compounds (VOCs), which are potentially harmful to air quality and human health. Therefore, the development of environmentally friendly glues has become one of the current research hotspots. Although some environmentally friendly heat-resistant glues on the market have reduced the use of harmful substances to a certain extent, they still have certain deficiencies in heat resistance and bonding strength. For example, some water-based glues are environmentally friendly, but their stability and durability at high temperatures are poor; while some high-performance heat-resistant glues may contain ingredients that are harmful to the human body. At present, most heat-resistant glues on the market are based on materials such as epoxy resin, polyurethane, and silicone resin. Although these materials have certain heat resistance, they still have some problems in practical applications. For example, epoxy resin may degrade or age at high temperatures, polyurethane is easy to soften at high temperatures, and silicone resin has limited adhesion. Therefore, based on the above problems, it is extremely necessary to develop an environmentally friendly heat-resistant glue. Summary of the invention

[0003] In view of the defects of the prior art, the object of the present invention is to provide an environmentally friendly heat-resistant glue and a preparation method thereof.

[0004] The technical effect described in the present invention is achieved through the following technical scheme: an environmentally friendly heat-resistant glue, which is composed of the following raw materials in parts by weight: 80 to 100 parts of polyvinyl chloride, 3 to 6 parts of nano-silicon dioxide, 4 to 8 parts of organic modified montmorillonite, 1 to 2 parts of amino graphene, 5 to 10 parts of polycaprolactone, 5 to 10 parts of polylactic acid, 10 to 20 parts of plasticizer and 0.5 to 1 part of antioxidant.

[0005] Preferably, the specific preparation steps of the amination graphene are as follows:

[0006] A1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the reaction temperature to 0-5°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add potassium permanganate, raise the temperature to 35-40°C after the addition is complete, stir and react for 12-24 hours, after the reaction is complete, slowly add deionized water to dilute, then add hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution for 3 times, dry at 60°C to constant weight, and obtain graphene oxide;

[0007] A2: The graphene oxide prepared in step A1 is dispersed in dimethyl sulfoxide, and ultrasonically treated at 200W for 30 to 60 minutes to obtain a graphene oxide dispersion; 3-aminopropyltriethoxysilane is slowly added dropwise to the graphene oxide dispersion, the temperature is controlled to 0 to 5°C and stirred continuously, after the addition is completed, the temperature is raised to 60°C, stirring is continued for 12 to 24 hours, centrifuged at 8000rpm for 10 minutes, washed repeatedly with deionized water and ethanol for 5 times, and dried at 60°C to constant weight to obtain amino graphene;

[0008] Preferably, in step A1, the ratio of the amount of graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-5mL:1g;

[0009] Preferably, in step A2, the ratio of the amount of graphene oxide, dimethyl sulfoxide and 3-aminopropyltriethoxysilane is 2 mg: 1-2 mL: 0.02-0.03 mL.

[0010] Preferably, the specific preparation steps of the organic modified montmorillonite are as follows:

[0011] B1: Add montmorillonite to deionized water, stir at 300 rpm for 30-60 min, and disperse evenly to obtain a montmorillonite dispersion; dissolve dodecyltrimethylammonium chloride in deionized water, and stir until completely dissolved to obtain an organic modified solvent;

[0012] B2: Slowly add the organic modified solvent prepared in step B1 to the montmorillonite dispersion, stir continuously at 300 rpm for 50 to 80 min, then heat to increase the temperature to 60 to 80° C., continue stirring for 1 to 2 h, centrifuge at 8000 rpm for 10 min, wash repeatedly with anhydrous ethanol for 3 times, and vacuum dry at 60° C. for 12 to 24 h to obtain organic modified montmorillonite;

[0013] Preferably, in step B1, the ratio of the amount of montmorillonite to deionized water is 1 g: 10-12 mL; the ratio of the amount of dodecyltrimethylammonium chloride to deionized water is 1-1.5 g: 100 mL;

[0014] Preferably, in step B2, the volume ratio of the organic modified solvent to the montmorillonite dispersion is 10:5-6.

[0015] Preferably, the plasticizer is any one of soybean oil, tributyl citrate, triethyl citrate and epoxidized soybean oil.

[0016] Preferably, the antioxidant is any one of ascorbic acid, 2,6-di-tert-butyl-p-cresol, diphenylamine and N-phenyl-α-naphthylamine.

[0017] Preferably, another aspect of the present invention is to provide a method for preparing an environmentally friendly heat-resistant glue, and the specific preparation steps are as follows:

[0018] S1: Dispersing nano-silicon dioxide, organic-modified montmorillonite and amino-modified graphene in plasticizer of the same weight, and performing ultrasonic dispersion treatment at 100-200W for 10-15min to obtain nano-silicon dioxide dispersion, organic-modified montmorillonite dispersion and amino-modified graphene dispersion respectively;

[0019] S2: adding polyvinyl chloride into a stirrer, then adding polycaprolactone and polylactic acid in sequence, raising the temperature to 80-100° C., stirring at a speed of 300-500 rpm for 30-60 min, then adding the nano-silicon dioxide dispersion, organically modified montmorillonite dispersion and amino-modified graphene dispersion prepared in step S1, and continuing stirring for 30 min to obtain a mixture;

[0020] S3: adding the remaining weight portions of plasticizer and antioxidant to the mixture prepared in step S2, controlling the temperature to 80-100° C., stirring at 300-500 rpm for 10-15 min, degassing, and cooling to room temperature to obtain glue;

[0021] Preferably, the parameters of the degassing treatment in step S3 are set to vacuum degree 0.08-0.1 MPa, temperature 25-35° C., and time 10-20 min.

[0022] The beneficial effects of the present invention are as follows:

[0023] The present invention significantly improves the heat resistance and mechanical properties of the glue by combining nano-silicon dioxide, organically modified montmorillonite and amino graphene. Nano-silicon dioxide is used as a basic thermally stable reinforcing material, and provides good thermal stability and mechanical support by filling and reinforcing the microstructure of the matrix; its fine particle size and high specific surface area enable it to be evenly dispersed in the matrix to form a stable network structure, further improving the overall strength and thermal stability of the material. The layered structure and good thermal stability of the organically modified montmorillonite effectively limit the thermal movement of polyvinyl chloride (PVC), prevent decomposition caused by heat accumulation, and effectively improve the high temperature resistance of the glue; through organic modification, the interlayer spacing of montmorillonite increases, significantly improving its compatibility and dispersibility with the polyvinyl chloride matrix, and further enhancing the thermal stability and mechanical properties of the material. Aminated graphene provides excellent thermal conductivity in the system, allowing the glue to quickly dissipate heat in a high temperature environment, reducing local thermal stress, and avoiding softening or flow of the material caused by heat accumulation. At the same time, the amino groups on the amination graphene interact with the polar groups in the polyvinyl chloride matrix to form chemical forces such as hydrogen bonds, which significantly improves the bonding strength of the glue; this bonding mechanism is particularly stable under high temperature conditions, effectively compensating for the decrease in bonding strength of polyvinyl chloride due to molecular slippage at high temperatures.

[0024] The present invention uses polycaprolactone and polylactic acid as flexible, bio-based toughening agents, so that the glue has good flexibility and environmental protection; polycaprolactone gives the material better ductility, and polylactic acid provides additional thermal stability. The two interact at the molecular level and toughen together, making the glue less brittle at high temperatures, thereby improving the durability during application. The addition of antioxidants further prevents the aging of polyvinyl chloride and extends the service life of the glue. Antioxidants effectively protect polymer chains from oxidation by capturing free radicals, interrupting oxidation chain reactions, etc., ensuring the stability of long-term bonding performance; at the same time, the chemical stability of amino graphene further enhances the overall antioxidant capacity. The layered structure of organically modified montmorillonite provides three-dimensional support for the material, effectively preventing the thermal decomposition of the material under high temperature conditions, and the layered structure of montmorillonite helps to absorb stress, while the rigid particles of nano-silicon dioxide provide compressive strength, so that the glue still maintains sufficient mechanical strength in a high temperature environment. The complementary effect of the two materials in microstructure significantly improves the overall performance of the glue; the combination of amino graphene and nano-silicon dioxide achieves a dual mechanical support and thermal conductivity synergistic effect. The high strength characteristics of amino graphene and the rigid structure of nano-silicon dioxide combine to make the glue have excellent impact resistance while improving the overall strength. The synergistic effect of each component achieves multi-level enhancement in heat resistance, mechanical strength, flexibility and anti-aging performance, ensuring the stable performance of the glue in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 It is a heat resistance analysis test result diagram of the glue prepared in Example 2 of the present invention and Comparative Examples 1 to 3;

[0027] Figure 2 It is a graph showing the VOCs release results of the long-term stability test of the glue prepared in Example 2 of the present invention and Comparative Examples 1 to 3;

[0028] Figure 3 1 is a graph showing the tensile strength test results of the glue prepared in Example 2 of the present invention and Comparative Examples 1 to 3;

[0029] Figure 4 It is a graph showing the elongation at break test results of the glue prepared in Example 2 of the present invention and Comparative Examples 1 to 3;

[0030] Figure 5 It is a graph showing the bonding strength test results of the glue prepared in Example 2 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.

[0032] Embodiment 1: An environmentally friendly heat-resistant glue, comprising the following raw materials in parts by weight: 80 parts of polyvinyl chloride, 3 parts of nano-silicon dioxide, 4 parts of organic modified montmorillonite, 1 part of amino graphene, 5 parts of polycaprolactone, 5 parts of polylactic acid, 10 parts of plasticizer and 0.5 parts of antioxidant.

[0033] The specific preparation steps of amination graphene are as follows:

[0034] A1: Add 10g of graphite powder to a flask, slowly add 200mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 5°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add 30g of potassium permanganate, after the addition is complete, raise the temperature to 35°C, stir and react for 12h, after the reaction is complete, slowly add 800mL of deionized water to dilute, then add 30mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution 3 times, dry at 60°C to constant weight, and obtain graphene oxide;

[0035] A2: Disperse 1000 mg of graphene oxide prepared in step A1 in 500 mL of dimethyl sulfoxide, and perform ultrasonic treatment at 200 W for 30 min to obtain a graphene oxide dispersion; slowly drop 10 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 5°C and continue stirring. After the dropwise addition is completed, heat to 60°C, continue stirring for 12 h, centrifuge at 8000 rpm for 10 min, wash repeatedly with deionized water and ethanol for 5 times, and dry at 60°C to constant weight to obtain amino graphene;

[0036] The specific preparation steps of organic modified montmorillonite are as follows:

[0037] B1: Add 50g of montmorillonite into 500mL of deionized water, stir at 300rpm for 30min to disperse evenly, and obtain a montmorillonite dispersion; dissolve 10g of dodecyltrimethylammonium chloride into 1000mL of deionized water, stir until completely dissolved, and obtain an organic modified solvent;

[0038] B2: Slowly add 1000 mL of the organic modified solvent prepared in step B1 to 500 mL of the montmorillonite dispersion, stir continuously at 300 rpm for 50 min, then heat to increase the temperature to 60°C, continue stirring for 2 h, centrifuge at 8000 rpm for 10 min, wash repeatedly with anhydrous ethanol 3 times, and vacuum dry at 60°C for 12 h to obtain organic modified montmorillonite;

[0039] The specific preparation steps of environmentally friendly heat-resistant glue are as follows:

[0040] S1: Dispersing nano-silicon dioxide, organic-modified montmorillonite and amino-modified graphene in soybean oil of the same weight, and performing ultrasonic dispersion treatment at 100W for 15min to obtain nano-silicon dioxide dispersion, organic-modified montmorillonite dispersion and amino-modified graphene dispersion respectively;

[0041] S2: adding polyvinyl chloride into a stirrer, then adding polycaprolactone and polylactic acid in sequence, raising the temperature to 80° C., stirring at a speed of 300 rpm for 60 min, then adding the nano-silica dispersion, organically modified montmorillonite dispersion and amino-modified graphene dispersion prepared in step S1, and continuing stirring for 30 min to obtain a mixture;

[0042] S3: Add the remaining weight portions of soybean oil and ascorbic acid to the mixture prepared in step S2, control the temperature to 80°C, stir at 300 rpm for 15 min, degas with parameters set as vacuum degree 0.1 MPa, temperature 25°C, time 20 min, and then cool to room temperature to obtain glue.

[0043] Example 2: An environmentally friendly heat-resistant glue, comprising the following raw materials in parts by weight: 100 parts of polyvinyl chloride, 6 parts of nano-silicon dioxide, 5 parts of organically modified montmorillonite, 2 parts of amino graphene, 10 parts of polycaprolactone, 10 parts of polylactic acid, 20 parts of plasticizer and 1 part of antioxidant.

[0044] The specific preparation steps of amination graphene are as follows:

[0045] A1: Add 10g of graphite powder to a flask, slowly add 250mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 4°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add 30g of potassium permanganate, raise the temperature to 40°C after the addition is complete, stir and react for 12h, after the reaction is complete, slowly add 1000mL of deionized water to dilute, then add 50mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution for 3 times, dry at 60°C to constant weight, and obtain graphene oxide;

[0046] A2: Disperse 1000 mg of graphene oxide prepared in step A1 in 1000 mL of dimethyl sulfoxide, and perform ultrasonic treatment at 200 W for 60 min to obtain a graphene oxide dispersion; slowly drop 15 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 4°C and continue stirring. After the dropwise addition is completed, heat to 60°C, continue stirring for 24 h, centrifuge at 8000 rpm for 10 min, wash repeatedly with deionized water and ethanol for 5 times, and dry at 60°C to constant weight to obtain amino graphene;

[0047] The specific preparation steps of organic modified montmorillonite are as follows:

[0048] B1: Add 50g of montmorillonite into 600mL of deionized water, stir at 300rpm for 60min, and disperse evenly to obtain a montmorillonite dispersion; dissolve 15g of dodecyltrimethylammonium chloride into 1000mL of deionized water, and stir until completely dissolved to obtain an organic modified solvent;

[0049] B2: Slowly add 1000 mL of the organic modified solvent prepared in step B1 to 600 mL of the montmorillonite dispersion, stir continuously at 300 rpm for 80 min, then heat to increase the temperature to 80°C, continue stirring for 1 h, centrifuge at 8000 rpm for 10 min, wash repeatedly with anhydrous ethanol 3 times, and vacuum dry at 60°C for 24 h to obtain organic modified montmorillonite;

[0050] The specific preparation steps of environmentally friendly heat-resistant glue are as follows:

[0051] S1: Dispersing nano-silicon dioxide, organic-modified montmorillonite and amino-modified graphene in tributyl citrate of the same weight, and subjecting to ultrasonic dispersion treatment at 200W for 10min to obtain nano-silicon dioxide dispersion, organic-modified montmorillonite dispersion and amino-modified graphene dispersion, respectively;

[0052] S2: adding polyvinyl chloride into a stirrer, then adding polycaprolactone and polylactic acid in sequence, raising the temperature to 100° C., stirring at a speed of 500 rpm for 30 min, then adding the nano-silicon dioxide dispersion, organically modified montmorillonite dispersion and amino-modified graphene dispersion prepared in step S1, and continuing stirring for 30 min to obtain a mixture;

[0053] S3: Add the remaining weight portions of tributyl citrate and 2,6-di-tert-butyl-p-cresol to the mixture prepared in step S2, control the temperature to 100°C, stir at 500 rpm for 10 min, degas with parameters set as vacuum degree 0.08 MPa, temperature 35°C, time 10 min, and then cool to room temperature to obtain glue.

[0054] Example 3: An environmentally friendly heat-resistant glue, comprising the following raw materials in parts by weight: 90 parts of polyvinyl chloride, 5 parts of nano-silicon dioxide, 8 parts of organically modified montmorillonite, 1.5 parts of amino graphene, 8 parts of polycaprolactone, 8 parts of polylactic acid, 18 parts of plasticizer and 0.8 parts of antioxidant.

[0055] The specific preparation steps of amination graphene are as follows:

[0056] A1: Add 10g of graphite powder to a flask, slowly add 230mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 0℃, stir and mix to disperse evenly, control the temperature to 10℃, slowly add 30g of potassium permanganate, after the addition is complete, raise the temperature to 37℃, stir and react for 20h, after the reaction is complete, slowly add 900mL of deionized water to dilute, then add 40mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution for 3 times, dry at 60℃ to constant weight, and obtain graphene oxide;

[0057] A2: Disperse 1000 mg of graphene oxide prepared in step A1 in 800 mL of dimethyl sulfoxide, and perform ultrasonic treatment at 200 W for 50 min to obtain a graphene oxide dispersion; slowly drop 13 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 0°C and continue stirring. After the dropwise addition is completed, heat to 60°C, continue stirring for 20 h, centrifuge at 8000 rpm for 10 min, wash repeatedly with deionized water and ethanol for 5 times, and dry at 60°C to constant weight to obtain amino graphene;

[0058] The specific preparation steps of organic modified montmorillonite are as follows:

[0059] B1: Add 50g of montmorillonite into 550mL of deionized water, stir at 300rpm for 50min, and disperse evenly to obtain a montmorillonite dispersion; dissolve 12g of dodecyltrimethylammonium chloride into 1000mL of deionized water, and stir until completely dissolved to obtain an organic modified solvent;

[0060] B2: Slowly add 1000 mL of the organic modified solvent prepared in step B1 to 550 mL of the montmorillonite dispersion, stir continuously at 300 rpm for 70 min, then heat to increase the temperature to 70°C, continue stirring for 1.5 h, centrifuge at 8000 rpm for 10 min, wash repeatedly with anhydrous ethanol 3 times, and vacuum dry at 60°C for 20 h to obtain organic modified montmorillonite;

[0061] The specific preparation steps of environmentally friendly heat-resistant glue are as follows:

[0062] S1: Dispersing nano-silicon dioxide, organic-modified montmorillonite and amino-modified graphene in the same weight proportion of epoxidized soybean oil, and subjecting to 150W ultrasonic dispersion treatment for 12 min to obtain nano-silicon dioxide dispersion, organic-modified montmorillonite dispersion and amino-modified graphene dispersion, respectively;

[0063] S2: adding polyvinyl chloride into a stirrer, then adding polycaprolactone and polylactic acid in sequence, raising the temperature to 90° C., stirring at a speed of 400 rpm for 50 min, then adding the nano-silicon dioxide dispersion, organically modified montmorillonite dispersion and amino-modified graphene dispersion prepared in step S1, and continuing stirring for 30 min to obtain a mixture;

[0064] S3: Add the remaining weight portions of epoxidized soybean oil and N-phenyl-α-naphthylamine to the mixture prepared in step S2, control the temperature to 90°C, stir at 400 rpm for 12 min, degas with parameters set at vacuum degree 0.09 MPa, temperature 30°C, time 15 min, and then cool to room temperature to obtain glue.

[0065] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that no organic modified montmorillonite is added in Comparative Example 1.

[0066] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that no amino-treated graphene is added in Comparative Example 2.

[0067] Comparative Example 3: The operation of Comparative Example 3 is substantially the same as that of Example 2, except that montmorillonite is used in Comparative Example 3 to replace the organic modified montmorillonite.

[0068] Performance Test:

[0069] Heat resistance analysis test: Take 10 mg of the glue prepared in Example 2 and Comparative Examples 1 to 3 and gradually heat it from 25°C to 600°C at a heating rate of 10°C / min, set the nitrogen flow rate to 20 mL / min, and record the thermal decomposition mass of the glue at 100°C, 200°C, 400°C and 600°C, that is, the percentage of sample mass reduction. The results are as follows: Figure 1 shown.

[0070] Depend on Figure 1 As can be seen from the results, the glue prepared by the present invention has excellent heat resistance and can maintain good stability at a relatively high temperature of 400°C; from the results of Comparative Example 1 and Example 2, it can be seen that without the protection of organic modified montmorillonite, the overall thermal stability of the material is affected, and the PVC chain may decompose significantly due to the lack of thermal stability support of the organic modified montmorillonite, thereby significantly increasing the mass loss; from the results of Comparative Example 2 and Example 2, it can be seen that due to the lack of thermal conductivity of amino graphene, local heat is difficult to dissipate. At the same time, after the amino graphene is missing, the decomposition temperature of PVC is low, and the lack of support for thermal conductivity and heat dissipation and the improvement of bonding strength may cause more obvious decomposition, thereby significantly increasing the mass loss; from the results of Comparative Example 3 and Example 2, due to the poor compatibility of ordinary montmorillonite with polyvinyl chloride matrix, the PVC molecular chain lacks effective support, and the thermal stability is affected. At the same time, due to the lack of three-dimensional structural support of organic modified montmorillonite, the carbonization residual rate is low, and the material's high temperature resistance is seriously insufficient.

[0071] Long-term stability test: 100 mg of glue prepared in Example 2 and Comparative Examples 1 to 3 was stored at 50°C and 80% humidity for 6 months, and the volatile organic compound (VOC) content in the glue was analyzed by gas chromatography-mass spectrometry at the 1st, 2nd, 3rd and 6th month. The results are as follows: Figure 2 shown.

[0072] Depend on Figure 2As can be seen from the results, the glue prepared by the present invention has excellent stability and environmental protection, and can be effectively used for a long time; from the results of Comparative Example 1 and Example 2, it can be seen that the compatibility and dispersibility enhancement effect of organic modified montmorillonite is lacking, which may lead to a higher plasticizer migration rate and a significant increase in VOCs release in the first few months; from the results of Comparative Example 2 and Example 2, it can be seen that the amino group provided by the amino graphene can not only interact with the PVC matrix to increase adhesion, but also reduce local temperature accumulation through its thermal conductivity. In the absence of amino graphene, the heat accumulation in the material increases, and the volatilization rate of plasticizers and other organic matter increases, which leads to a significant increase in VOCs release; from the results of Comparative Example 3 and Example 2, it can be seen that the dispersibility and interfacial bonding of the unmodified montmorillonite are insufficient, and the stabilizing effect on the matrix structure is not as good as that of the organic modified montmorillonite, which may also lead to increased migration and volatility of the plasticizer, thereby leading to an increase in VOCs release.

[0073] Mechanical strength test: The tensile strength and elongation at break of the glue prepared in Example 2 and Comparative Examples 1 to 3 were tested using a tensile testing machine. The results are as follows: Figure 3 and Figure 4 shown.

[0074] Depend on Figure 3 and Figure 4 It can be seen from the results that the glue prepared by the present invention has excellent mechanical strength and ductility; from the results of Comparative Example 1 and Example 2, it can be seen that the lack of organic modified montmorillonite may lead to reduced layered structural support and compatibility of the material, thereby leading to a decrease in mechanical strength and ductility; from the results of Comparative Example 2 and Example 2, it can be seen that the amino group of the amination graphene can enhance the adhesion with PVC, so that the elongation at break of the whole material during the stretching process is improved. After the amination graphene is lacking, the tensile strength is reduced and the elongation at break is significantly reduced; from the results of Comparative Example 3 and Example 2, it can be seen that the unmodified montmorillonite has a poor dispersion effect, which may affect the uniformity and flexibility of the material, making it more likely to experience local stress concentration and break during stretching, thereby leading to a decrease in elongation at break.

[0075] Bond strength test: The bond strength of the glue prepared in Example 2 and Comparative Examples 1 to 3 was tested using a peel test (ASTM D1876) at 25°C, 100°C and 200°C. The results are as follows: Figure 4 shown.

[0076] Depend on Figure 4As a result, the glue prepared by the present invention can still maintain good bonding strength at a relatively high temperature. From the results of Comparative Example 1 and Example 2, it can be seen that the lack of organically modified montmorillonite restricts the thermal movement of polyvinyl chloride (PVC), which may lead to heat accumulation and decomposition, resulting in a significant decrease in the bonding strength of the glue at high temperatures; from the results of Comparative Example 2 and Example 2, it can be seen that the amino groups of the amino graphene form chemical forces such as hydrogen bonds with the polar groups in the PVC matrix, which significantly improves the bonding strength of the glue. The lack of amino graphene makes the bonding mechanism of the glue unstable, especially under high temperature conditions, PVC may cause a significant decrease in bonding strength at high temperatures due to molecular slip; from the results of Comparative Example 3 and Example 2, it can be seen that the compatibility and dispersibility of the unmodified montmorillonite with the PVC matrix are low, resulting in uneven dispersion of the montmorillonite in the glue. At the same time, the unmodified montmorillonite fails to form a synergistic effect with the amino graphene and nano-silica in the system, which may lead to a decrease in the bonding strength of the glue.

[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An environmentally friendly heat-resistant glue, characterized in that: The composition includes the following raw materials in parts by weight: 80-100 parts of polyvinyl chloride, 3-6 parts of nano silicon dioxide, 4-8 parts of organic modified montmorillonite, 1-2 parts of amino graphene, 5-10 parts of polycaprolactone, 5-10 parts of polylactic acid, 10-20 parts of plasticizer and 0.5-1 part of antioxidant; The specific preparation steps of the amino graphene are as follows: A1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the reaction temperature, stir and mix to disperse evenly, control the temperature, slowly add potassium permanganate, increase the temperature, stir and react, after the reaction is complete, slowly add deionized water to dilute, then add hydrogen peroxide to terminate the reaction, centrifuge, repeatedly wash with deionized water and HCl solution, dry to constant weight, and obtain graphene oxide; A2: Disperse the graphene oxide prepared in step A1 in dimethyl sulfoxide, and perform ultrasonic treatment to obtain a graphene oxide dispersion; slowly drop 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature and continue stirring, and after the dropwise addition is completed, heat up, continue stirring, centrifuge, repeatedly wash with deionized water and ethanol, and dry to constant weight to obtain amino graphene.

2. The environmentally friendly heat-resistant glue according to claim 1, characterized in that: In step A1, the ratio of the amount of the graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-5mL:1g.

3. The environmentally friendly heat-resistant glue according to claim 2, characterized in that: In step A2, the ratio of the amount of graphene oxide, dimethyl sulfoxide and 3-aminopropyltriethoxysilane is 2 mg: 1-2 mL: 0.02-0.03 mL.

4. The environmentally friendly heat-resistant glue according to claim 3, characterized in that: The specific preparation steps of organic modified montmorillonite are as follows: B1: adding montmorillonite to deionized water, stirring and dispersing uniformly to obtain a montmorillonite dispersion; dissolving dodecyltrimethylammonium chloride in deionized water, stirring until completely dissolved, to obtain an organic modified solvent; B2: Slowly add the organic modified solvent prepared in step B1 to the montmorillonite dispersion, continue stirring, then heat to increase the temperature, continue stirring, centrifuge, repeatedly wash with anhydrous ethanol, and vacuum dry to obtain organic modified montmorillonite.

5. The environmentally friendly heat-resistant glue according to claim 4, characterized in that: In step B1, the ratio of the amount of montmorillonite to deionized water is 1 g: 10-12 mL; the ratio of the amount of dodecyltrimethylammonium chloride to deionized water is 1-1.5 g: 100 mL; in step B2, the volume ratio of the organic modified solvent to the montmorillonite dispersion is 10:5-6.

6. The environmentally friendly heat-resistant glue according to claim 5, characterized in that: The plasticizer is any one of soybean oil, tributyl citrate, triethyl citrate and epoxidized soybean oil.

7. The environmentally friendly heat-resistant glue according to claim 6, characterized in that: The antioxidant is any one of ascorbic acid, 2,6-di-tert-butyl-p-cresol, diphenylamine and N-phenyl-α-naphthylamine.

8. A method for preparing the environmentally friendly heat-resistant glue according to any one of claims 1 to 7, characterized in that: The specific preparation steps are as follows: S1: dispersing nano-silicon dioxide, organic-modified montmorillonite and amino-treated graphene in plasticizers of the same weight, and performing ultrasonic dispersion treatment to obtain nano-silicon dioxide dispersion, organic-modified montmorillonite dispersion and amino-treated graphene dispersion, respectively; S2: adding polyvinyl chloride into a stirrer, then adding polycaprolactone and polylactic acid in sequence, raising the temperature, stirring, then adding the nano-silicon dioxide dispersion, organically modified montmorillonite dispersion and amino graphene dispersion prepared in step S1, continuing stirring to obtain a mixture; S3: adding the remaining weight portions of plasticizer and antioxidant to the mixture prepared in step S2, controlling the temperature, stirring, degassing, and cooling to room temperature to obtain glue.

9. A method for preparing the environmentally friendly heat-resistant glue according to claim 8, characterized in that: The parameters of the degassing treatment in step S3 are set as vacuum degree 0.08-0.1 MPa, temperature 25-35° C., and time 10-20 min.

Citation Information

Patent Citations

  • Polychloroethylene / organic modified sheet silicate nano-composite material

    CN101302318A

  • PVC resin adhesive for ceramics and preparation method thereof

    CN101608102A

  • Antistatic flame-resistant environmentally stable peelable protective film and preparation method thereof

    CN102219965A

  • Heat curing adhesive for oil filter and preparation method of heat curing adhesive

    CN106634709A

  • Wear-resistant rubber and plastic composite material

    CN116606488A

Cited By

  • Polyvinyl chloride packaging adhesive containing polycaprolactone glycol and preparation method thereof

    CN120349736A